2001
DOI: 10.1038/sj.bmt.1702738
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of congenital erythropoietic porphyria in children by allogeneic stem cell transplantation: a case report and review of the literature

Abstract: Summary:Congenital erythropoietic porphyria (CEP) is a rare autosomal recessive disorder of porphyrin metabolism in which the genetic defect is the deficiency of uroporphyrinogen III cosynthase (UIIIC). Deficiency of this enzyme results in an accumulation of high amounts of uroporphyrin I in all tissues leading to hemolytic anemia, splenomegaly, erythrodontia, bone fragility, exquisite photosensitivity and mutilating skin lesions. We describe the case of a 23-month-old boy who was cured of his CEP by a matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 26 publications
0
50
0
2
Order By: Relevance
“…This human inborn error of heme biosynthesis is primarily an erythroid disease, since successful bone marrow or hematopoietic stem cell transplantation is curative (18) and since a hepatic-specific UROS deficiency did not compromise hemoprotein function (21). Because of the rarity of the disease, the extremely variable phenotypic expression and the limits of human experimentation, few hematologic studies of severe and later-onset CEP patients were reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This human inborn error of heme biosynthesis is primarily an erythroid disease, since successful bone marrow or hematopoietic stem cell transplantation is curative (18) and since a hepatic-specific UROS deficiency did not compromise hemoprotein function (21). Because of the rarity of the disease, the extremely variable phenotypic expression and the limits of human experimentation, few hematologic studies of severe and later-onset CEP patients were reported.…”
Section: Discussionmentioning
confidence: 99%
“…Additional manifestations often include hypertrichosis, alopecia and erythrodontia. Successful bone marrow or hematopoietic stem cell transplantation is essentially curative but is associated with increased morbidity and mortality (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…It manifests in the first year of life with severe photosensitivity, which causes bullae formation and mutilating scarring, in addition to erythrodontia, bone fragility, hemolytic anemia, ocular involvement, and hypertrichosis. Stem cell transplantation has been reported as a curative therapy (28). Importantly, prompt diagnosis should be made if possible in these newborns, with absolute contraindication of phototherapy for treatment of neonatal jaundice to avoid a widespread acute phototoxic bullous reaction (26).…”
Section: Metabolic Disorders and Genodermatoses Causing Photosensitivitymentioning
confidence: 99%
“…Other treatment modalities with limited efficacy include oral beta carotene, intravenous hematin, plasmapheresis, hydroxychloroquine, oral charcoal, and other porphyrin binders. 2,17 For severely affected patients who are transfusion dependent, erythrocyte transfusion, 18 hydroxyurea, 19 and splenectomy 20 appear effective, at least until adolescence; stem cell or bone marrow transplantation has been curative. 20,21 In vitro gene transfer studies have demonstrated restoration of URO-synthase activity, suggesting the future potential effectiveness of gene therapy.…”
Section: Commentmentioning
confidence: 99%
“…2,17 For severely affected patients who are transfusion dependent, erythrocyte transfusion, 18 hydroxyurea, 19 and splenectomy 20 appear effective, at least until adolescence; stem cell or bone marrow transplantation has been curative. 20,21 In vitro gene transfer studies have demonstrated restoration of URO-synthase activity, suggesting the future potential effectiveness of gene therapy. [22][23][24] In summary, we describe 2 brothers with CEP who have an unusually mild phenotype due to a novel heterozygous genotype that consists of a promoter mutation (−76G→A) and an exonic missense mutation (G225S).…”
Section: Commentmentioning
confidence: 99%